PENGELOLAAN ARSIP INAKTIF KEUANGAN KANTOR PELAYANAN PERBENDAHARAAN NEGARA DI KABUPATEN PURWOREJO - , ANIS SULISTYORINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Knowledge regarding archives are now experiencing a lot of progress. Not only in archival institution itself that implements a particular system in order to organize their files. Many kinds archival management learned and can be applied in offices. In this report, explained about records management in Kantor Pelayanan Perbendaharaan Negara (KPPN) Purworejo. Archives management in KPPN Purworejo especially inactive records management, using multiple management systems, depending on each section. This is caused KPPN Purworejo used decentralized system, therefore each section has a right to determine how the archival storage system. Archival storage system include the chronological system, codic system, and serial number system. From the results of fieldwork practices that writerâs did for two months, archival management in KPPN Purworejo been good. Just because the officer who manage archival record donât have special education in archives, their performance isnât maximized. The officers are still overwhelmed managing records that growing fastly.